A Programming Disposition Scale for High School Students - Chiu-Fan Hu; Yu-Tzu Lin; Cheng-Chih Wu; Hsueh-Chih Chen (Educational Technology & Society, 2022)
This study developed a scale to assess high school students’ programming disposition. The scale was developed by utilizing a standardized test development process. The three constructs of the scale, namely confidence, persistence and flexible thinking, consisted of 9 items (3 items on each construct). Participants for the formal test of the scale were 1,332 students from 11 high schools. The validity and reliability of the programming disposition scale were validated via internal consistency, test-retest reliability, construct validity, discriminant validity, criterion-related validity, correlation coefficient of each subscale and confirmatory factor analysis. The analysis results showed that this scale is valid and reliable. The scale can serve as an assessment tool to assist teachers to instruct students learning programming, and help students determine whether taking programming courses in high school or pursuing programming-related majors in university. The effects of individual differences on programming disposition were also discussed to provide feasible educational implications.